A COMPARATIVE STUDY OF MELATONIN WITH PLACEBO IN ATTENUATION OF HEMODYNAMIC RESPONSES TO LARYNGOSCOPY AND INTUBATION - Jamwal, Preeti; Ali, Zulfiqar; Chib, Mohinder Singh; Jamwal, Deepika; Nazir, Iqra; Lone, Abdul Qayoom; Aarif, Sajad (Sanamed, 2024)
Introduction: An increase in blood pressure and heart rate is observed during laryngoscopy and insertion of the endotracheal tube. Melatonin is used for sedation in the Intensive Care Unit. Our study was based on the hypothesis that administrating 3 mg and 6 mg of melatonin 90 minutes before induction attenuates hemodynamic responses encountered during laryngoscopy and intubation. Materials and Methods: Seventy-five adult patients scheduled for elective surgical procedures, ASA I and II, were assigned into 3 groups (25 patients in each group) to receive oral placebo, melatonin 3 mg, or melatonin 6 mg 90 minutes prior to induction of anesthesia. Hemodynamic variables were recorded at baseline, before induction, and at 3, 6, 9, 12, 15, and 30 minutes after induction. Analysis of variance (ANOVA) was used for intergroup analysis of data. Categorical variables were compared using non-parametric tests like the Chi-square test or Fisher’s exact test. Bonferroni correction was applied for intergroup analysis. Statistical significance was considered when p < 0.05. Results: An increase in heart rate and blood pressure at 3, 6, and 9 minutes after induction of general anesthesia was observed in the control group compared to the melatonin 3 mg and 6 mg groups administered 90 minutes prior to induction. Oral administration of 6 mg of melatonin was found to provide greater attenuation than 3 mg of melatonin. Conclusion: Oral administration of 3 mg and 6 mg melatonin effectively attenuates the hemodynamic pressor changes observed during laryngoscopy and tracheal intubation.